Heavy metals in soil contaminated with aluminum black dross waste in Jombang Regency, East Java - Lukita, Maya; Abidin, Zaenal; Riany, Etty; Ismail, Ahyar (Journal of Degraded and Mining Lands Management, 2025)
Aluminum waste recycling activities in Sumobito District, Jombang Regency, produce aluminum black dross that is classified as hazardous waste. Aluminum black dross dumped into the environment will become a potential hazard to human health and environmental quality. This study aimed to determine the soil condition at aluminum black dross landfills in Sumobito District. Soil quality was determined by comparing the concentration of heavy metals in the samples with the total concentration (TC) of heavy metal pollutants regulated by the Government Regulation of the Republic of Indonesia No. 22 of 2021. Soil samples were analyzed using X-ray fluorescence (XRF). The analysis of four landfill samples showed that all samples should be managed as hazardous waste. The analysis of soil samples carried out around the landfill area shows that three samples are managed as non-hazardous waste, and one soil sample must be managed as hazardous waste. This indicates that heavy metal infiltration of aluminum black dross from the landfill area into the soil area has occurred.